Aerogel porous cement-based sound-absorbing material and method for its preparation

CN122916561APending Publication Date: 2026-10-16CHENGDU ZHONGHONG RAIL TRANSIT ENVIRONMENTAL PROTECTION IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611387876.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本申请公开了一种气凝胶多孔水泥基吸声材料及其制备方法,以解决现有技术中水泥基吸声材料吸声频带窄、力学性能与吸声性能难以兼顾、孔结构调控手段单一、气凝胶与水泥基体相容性差的问题

Benefits of technology

1、本发明通过特制陶粒大孔、引气中孔和二氧化硅气凝胶纳米孔的三级孔结构协同作用,实现了对低、中、高频声波的宽频高效吸收,材料厚度4cm时,降噪系数NRC可达0.68-0.78,平均吸声系数≥0.65;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of sound-absorbing noise-reducing materials, and discloses an aerogel porous cement-based sound-absorbing material and a preparation method thereof. The application is characterized in that: special ceramic granules are pretreated, and an aerogel dispersion liquid is prepared; dry mixed materials are prepared by stirring and mixing silicate cement, silica fume and redispersible emulsion powder; water-reducing agent, air entraining agent and foam stabilizer are added into the aerogel dispersion liquid and stirred and mixed with the dry mixed materials to prepare cement cementation slurry; the specially-prepared ceramic granules after pre-wetting treatment are added into the cement cementation slurry and stirred and mixed to prepare mixed materials; and the mixed materials are poured into a mold for shaping and curing. The obtained silica aerogel porous cement-based sound-absorbing material has a wide sound-absorbing frequency band and a high sound-absorbing coefficient, has excellent mechanical properties and sound-absorbing properties, and has a controllable multi-stage pore structure; the aerogel has good compatibility with the cement matrix, and is suitable for various noise scenes such as sound barriers, tunnel inner walls, building outer walls and industrial workshops.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sound-absorbing and noise-reducing materials, and in particular to an aerogel porous cement-based sound-absorbing material and its preparation method. Background Technology

[0002] With the acceleration of urbanization and the rapid development of the transportation industry, traffic noise pollution has become increasingly serious, posing a significant environmental problem affecting the quality of the living environment and the physical and mental health of the public. Cement-based sound-absorbing materials, due to their wide availability of raw materials, ease of construction, and good fire resistance, have broad application prospects in noise control projects such as high-speed railway sound barriers, tunnel walls, building sound insulation walls, urban rail transit sound-absorbing panels, and industrial plants.

[0003] Currently, existing cement-based porous sound-absorbing materials are mainly prepared by chemical foaming, physical foaming, or adding lightweight aggregates. However, cement-based sound-absorbing materials prepared by the above methods have narrow sound absorption frequency bands, difficulty in achieving both mechanical and sound absorption properties, limited means of pore structure control, and poor compatibility between aerogel and cement matrix. Summary of the Invention

[0004] This application discloses an aerogel porous cement-based sound-absorbing material and its preparation method, in order to solve the problems of narrow sound absorption frequency band, difficulty in balancing mechanical properties and sound absorption properties, limited means of pore structure control, and poor compatibility between aerogel and cement matrix in the prior art.

[0005] To solve the above problems, the present invention adopts the following technical solution: An aerogel porous cement-based sound-absorbing material, the raw materials of which, by weight, include: 100 parts silicate cement, 80-150 parts special ceramsite, 5-25 parts silica aerogel, 10-30 parts silica fume, 2-8 parts redispersible latex powder, 1-3 parts water-reducing agent, 0.5-2 parts air-entraining agent, 0.1-0.5 parts foam stabilizer, and 45-65 parts water; Specifically, the silicate cement is P.O42.5R, which serves as the cementitious matrix, ensuring the material's basic compressive and flexural strength and preventing pore collapse and material pulverization. The micron-level interconnected pores within the specially formulated ceramsite, after accumulation, form millimeter-level pores between the particles, constructing large-size, interconnected sound-absorbing channels and broadening the low-frequency sound absorption band. Silica aerogel significantly enhances the mid-to-high frequency sound absorption coefficient, and its uniform dispersion in the cement slurry prevents the nanopores from being blocked by the cement slurry, preserving the complete sound-absorbing pore structure. Silica fume fills the gaps between cement particles and aerogel powder, optimizing the interfacial bonding force and preventing aerogel detachment and agglomeration, fundamentally solving the problem of poor compatibility between aerogel and the cement matrix. It also fills the large pore gaps, constructing numerous submicron-level transition pores, perfecting the multi-level pore gradient, and finely controlling the micropore structure, thereby improving the material's compressive and flexural strength and achieving a balance between sound absorption and mechanical properties. Redispersible latex powder is distributed throughout the slurry. The aerogel-ceramsite interface counteracts cement brittleness, enhances the material's flexural and impact toughness, and prevents cracking and collapse under stress, ensuring the integrity of the porous structure, improving hydrophobicity, and aiding in improved compatibility. A water-reducing agent ensures uniform dispersion of the aerogel in the matrix, preventing localized aerogel enrichment and absence, guaranteeing uniform overall sound absorption performance while reducing the water-cement ratio and maintaining the material's mechanical strength. An air-entraining agent introduces microbubbles during mixing, and a foam stabilizer enhances the stability of these bubbles in the cement paste. Together with the interconnected macropores of the ceramsite, they form a multi-level porous structure of "macropores (ceramsite gaps) - mesopores (air-entraining bubbles) - nanopores (aerogel)," achieving efficient absorption of broadband sound waves. The foam stabilizer liquid film and the latex powder polymer film provide dual protection for the micropores, preventing pore collapse throughout the curing process. Water is used for mixing, providing a liquid environment for powder dispersion and bubble generation. Combined with the water-reducing agent, the water-cement ratio is precisely controlled, balancing moldability, pore structure, and mechanical strength.

[0006] Among them, the silica aerogel is a hydrophobic nano silica aerogel powder with a particle size of 20-100nm and a porosity of ≥90%.

[0007] Specifically, the hydrophobic nano-silica aerogel powder has a specific surface area ≥600m² / g and a thermal conductivity ≤0.020W / (m·K), providing ultra-high porosity nanopores (loss of high-frequency sound waves). Combined with the stacking of specially made ceramic particles to generate millimeter-scale macropores (loss of low-frequency sound waves) and the generation of uniform micron-scale pores by air-entraining agent and foam stabilizer (loss of mid-frequency sound waves), a three-level gradient interconnected pore structure is constructed, which greatly broadens the effective sound absorption frequency band and significantly improves the sound absorption coefficient across the entire frequency band.

[0008] Dense CSH gel is generated by reacting silicate cement with silica fume and volcanic ash, which improves the compressive strength of the matrix and offsets the strength loss caused by the porous structure. At the same time, it can redisperse latex powder to form a flexible polymer film, improve the brittleness of the material, and enhance the flexural and impact toughness, making the porous structure less prone to cracking under stress. Meanwhile, specially made ceramsite acts as a rigid skeleton to bear the main load, achieving a balance between sound absorption and mechanical properties.

[0009] By adjusting the dosage of specially formulated ceramic particles, millimeter-level packing pores can be controlled. Through the synergistic effect of air-entraining agents and foam stabilizers, the size and number of micron-sized bubbles can be precisely controlled. By adjusting the dosage of hydrophobic nano-silica aerogel, nano-level ultra-high porosity can be controlled. Water-reducing agents can be used to adjust the water-cement ratio to assist in pore adjustment and change the secondary pores formed by the evaporation of excess free water. Through the synergy of multiple methods, the multi-level pore structure can be flexibly adjusted according to the application scenario.

[0010] The aerogel nanoparticles are fully preserved by using hydrophobic nano-silica aerogel powder; silica fume is used to fill the gaps between the aerogel and the cement matrix, and volcanic ash reacts to generate CSH gel, anchoring the aerogel particles in the matrix and preventing aerogel powder from falling off or delaminating; water-reducing agent is used to eliminate the agglomeration of the nano-aerogel particles, achieving uniform dispersion of the aerogel in the cement matrix; redispersible latex powder is used to further strengthen the bonding force between the aerogel and the cement paste interface; and the combination of hydrophobic nano-silica aerogel with silica fume, water-reducing agent, and redispersible latex powder optimizes interfacial compatibility, improves overall compatibility, and solves the problem of poor compatibility between aerogel and cement matrix.

[0011] Furthermore, the specially prepared ceramsite is a high-strength ceramsite that has undergone surface modification treatment. It is made from fly ash, clay or shale as raw materials, and is granulated and sintered at high temperature to produce ceramsite raw material with a particle size controlled at 0.5-2.0 mm. Then, the ceramsite raw material is soaked in an ethanol solution of silane coupling agent for 30-60 min, and then dried at 80-100℃ for 2-4 h to obtain surface-modified ceramsite.

[0012] Specifically, the high-temperature sintering temperature is 1100-1250℃. After high-temperature sintering, a ceramic solid-phase skeleton is formed inside, significantly improving the compressive strength of the ceramsite. The particle size of the ceramsite raw material is controlled at 0.5-2.0mm to precisely construct the large-size interconnected pores required for low-frequency sound absorption, broadening the low-frequency sound absorption band. At the same time, the aggregate uniformly disperses the internal stress of the matrix, inhibiting microcracks caused by cement hardening shrinkage. The compressive strength of the ceramsite raw material is ≥5MPa, and the water absorption rate is 12-25% in 1 hour. The ethanol solution mass concentration of the silane coupling agent (KH-550) is 2-5%. One end of the silane coupling agent is an inorganic silanol group, which can chemically bond with the ceramic phase and silica components on the surface of the ceramsite; the other end is an organic hydrophobic functional group, which can bind with silica fume in cement slurry. Hydrophobic silica aerogel and redispersible latex powder are compatible with the organic phase, building an interfacial bridge between inorganic ceramsite, cement matrix, and aerogel filler. Ethanol is used as a dispersion medium to reduce the viscosity of the silane coupling agent, allowing it to uniformly wet and coat the entire inner and outer surfaces of the ceramsite and penetrate into the inner walls of the micron-sized pores within the ceramsite itself, avoiding incomplete local modification. Sufficient soaking time ensures that the ceramsite surface fully adsorbs silane molecules, forming a complete modified coating layer. Low-temperature drying at 80-100℃ for 2-4 hours slowly evaporates the ethanol solvent, preventing rapid evaporation that could cause the silane coating layer to crack or agglomerate. At the same time, this temperature range promotes a dehydration condensation reaction between the silane coupling agent and the ceramsite surface, forming strong chemical bonds. The modified layer is not easily detached or washed away, achieving long-term interfacial modification.

[0013] Modified ceramsite improves the compatibility between ceramsite and cement matrix, eliminates interface defects, protects the original sound-absorbing micropores inside the ceramsite, prevents cement slurry blockage, and synergistically enhances the dispersion stability of aerogel in the system, solves the problem of poor aerogel compatibility, strengthens mechanical properties, and maximizes the balance between sound absorption and strength.

[0014] Furthermore, the redispersible latex powder is an ethylene-vinyl acetate copolymer.

[0015] Specifically, ethylene-vinyl acetate copolymer (EVA) forms a continuous, highly elastic polymer film at the interface of cement slurry, ceramsite, and aerogel particles. This film buffers and disperses load stress, significantly improving the material's flexural strength and impact toughness. It avoids the problems of easy breakage and pulverization of materials with high porosity and high aerogel content, and enhances sound absorption and mechanical properties. At the same time, the EVA liquid uniformly coats the pore walls of each level of pores, forming an elastic support film that prevents free calcium ions and hydrated ultrafine particles inside the cement from penetrating into the nanopores of the aerogel, preventing nanopore blockage and ensuring the long-term sound absorption capacity of the aerogel. The EVA film fills the tiny gaps between silica fume and cement particles, and together with the CSH gel generated by the reaction of silica fume and volcanic ash, it forms a dual interface anchoring structure of "inorganic rigid bonding + organic flexible bonding," solving the problem of delamination at the interface between aerogel and modified ceramsite. It also complements the low-frequency loss of the large pores of ceramsite and the high-frequency loss of the nanopores of aerogel, further broadening the effective sound absorption frequency band of the material. It works synergistically with air-entraining agents and foam stabilizers to create pores, resulting in stable and controllable pore size.

[0016] Furthermore, the water-reducing agent is a polycarboxylate water-reducing agent.

[0017] Specifically, polycarboxylate molecules adsorb onto the surfaces of cement particles, silica fume, and silica aerogel powder, forming a thick spatial barrier layer with long side chains. This counteracts the van der Waals adsorption forces between ultrafine particles while providing electrostatic repulsion, completely breaking up powder agglomerates. Furthermore, the high dispersion efficiency of the polycarboxylate superplasticizer allows for a significant reduction in mixing water consumption, achieving low water-cement ratio molding, while maintaining consistent slurry fluidity and meeting casting requirements. The polycarboxylate superplasticizer itself has extremely low air entrainment, introducing almost no extra stray air bubbles. Even at a low water-cement ratio, the polycarboxylate superplasticizer imparts high fluidity and self-leveling properties to the slurry, preventing viscous lumps and making it less prone to stratification and segregation during casting and precasting. After molding, the internal pores are uniformly distributed, without local voids or dense areas, resulting in consistent sound absorption and mechanical properties in the finished product, reducing product scrap rates.

[0018] Furthermore, the air-entraining agent is rosin thermal polymer or sodium dodecyl sulfate.

[0019] Specifically, the rosin thermal polymer air-entraining agent stably generates uniform microbubbles of 20-200μm during the stirring process. These bubbles are not easily merged into super-large pores, and the bubble liquid film is resistant to the highly alkaline environment of cement. It is not easy to break the bubbles in the strongly alkaline environment of cement hydration, and the porosity is stable after molding. The sodium dodecyl sulfate air-entraining agent will foam rapidly and form high-density ultrafine micro-pores in the slurry, filling the pore layer between the macropores of ceramsite and the nanopores of aerogel. When used with a foam stabilizer, the bubble distribution density can be controlled, and the proportion of mid-frequency sound-absorbing pores can be precisely adjusted.

[0020] Furthermore, the foam stabilizer is hydroxypropyl methylcellulose ether.

[0021] Specifically, hydroxypropyl methylcellulose ether (HPMC) increases the viscosity of the liquid phase of the slurry after dissolving in water. At the same time, the polymer chain segments are adsorbed on the surface of the bubble liquid film formed by the air-entraining agent, forming a highly elastic and tough composite protective film. In addition, the hydrophilic groups of HPMC molecules have extremely strong water-locking ability, which can stably bind the mixing water inside the slurry and slow down the rapid evaporation of water. HPMC also contains hydrophobic methyl groups, so it will not be adsorbed and accumulated in large quantities on the surface of hydrophobic silica aerogel and special ceramic particles, and will not damage the hydrophobic film on the surface of the filler. Furthermore, by adjusting the amount of HPMC, the viscosity of the slurry and the toughness of the bubble liquid film can be precisely adjusted, and the crack resistance of the material can be slightly improved, synergistically balancing the sound absorption performance and mechanical strength.

[0022] The preparation method of the above-mentioned aerogel porous cement-based sound-absorbing material includes the following steps: S1. Pretreatment of special ceramsite: Rinse the special ceramsite with clean water to remove surface dust, soak it in water for 1-2 hours for pre-wetting treatment, take it out and drain it until it is saturated and dry, and set it aside. Specifically, the above treatment prevents dust from clogging the original micron-sized sound-absorbing pores of the ceramsite, fully preserves the low-frequency sound-absorbing channels, eliminates the problem of water absorption and competition of the ceramsite, improves the uniformity of the ceramsite coating, and inhibits interface water loss, shrinkage, and cracking during the molding and curing stage.

[0023] S2. Preparation of aerogel dispersion: Add silica aerogel powder to a portion of water at a mass ratio of 1:2-10, and add 0.5-2% of polycarboxylate superplasticizer by mass of silica aerogel. The aerogel dispersion is prepared by a combination of high-speed shear dispersion and ultrasonic dispersion. The high-speed shearing speed is 3000-5000 rpm and the dispersion time is 10-30 min. The ultrasonic frequency is 40-80 kHz and the dispersion time is 5-15 min.

[0024] Specifically, by pre-treating the aerogel to completely break down the aerogel aggregates, the nanopores inside the aerogel are protected from being blocked, and the concentration of the dispersion is controllable to adapt to different aerogel dosages. The surface of the aerogel particles is pre-coated with water-reducing agent molecules, and after being mixed into cement mortar, it continues to maintain a dispersed state. The aerogel is evenly distributed inside the finished product, and the overall sound absorption performance of the material has no local differences.

[0025] S3. Dry material mixing: Weigh silicate cement, silica fume, and redispersible latex powder according to the mass ratio, place them in a mixer, and mix at low speed for 2-3 minutes to ensure that all components are fully mixed and uniform, thus obtaining a dry mixture; the speed of the low-speed mixer is 60-100 rpm.

[0026] Specifically, silica fume is evenly interspersed between cement particles, and EVA latex powder is evenly dispersed in the dry material. This prevents localized clumping of latex powder upon contact with water, ensuring uniform distribution of the flexible EVA polymer film throughout the hardened material. It also reduces the subsequent liquid phase stirring load, shortens the stirring time, and reduces the risk of air bubbles bursting during prolonged stirring. The silica fume is premixed with cement, allowing it to fully utilize its pozzolanic activity during the hydration stage, continuously generating CSH gel to strengthen the interface and improve the material's mechanical strength.

[0027] S4. Slurry preparation: Mix the aerogel dispersion obtained in S2 with the remaining water, and add polycarboxylate superplasticizer, air-entraining agent and foam stabilizer. After stirring evenly, slowly add it to the dry mixture obtained in S3. Stir at low speed for 1-2 minutes, and then stir at high speed for 3-5 minutes to obtain cement slurry. The stirring speed at low speed is 60-100 rpm, and the stirring speed at high speed is 200-400 rpm.

[0028] Specifically, by pre-dissolving water-reducing agents, air-entraining agents, and foam stabilizers in the aerogel dispersion, there is no localized excessively high or low concentration of additives. The foaming, foam stabilization, and dispersion effects are uniform throughout the entire process. Low-speed stirring achieves initial wetting and mixing of the dry powder, preventing splashing of the slurry and the collapse of a large number of bubbles in the initial stage of high-speed stirring. Subsequent high-speed stirring further breaks up the agglomeration of tiny powder particles, while uniformly introducing a large number of stable micron-sized bubbles to construct mid-frequency sound-absorbing pores. This process protects the dispersion state of the aerogel throughout, ensuring that the nano-sound-absorbing pores remain intact.

[0029] S5, Expanded clay aggregate coating: Add the special expanded clay aggregate that has been pre-wetted in S1 to the cement slurry prepared in S4, stir for 2-4 minutes to make the surface of the special expanded clay aggregate uniformly coated with cement slurry to obtain the mixture. Specifically, after the cement slurry is formed, ceramsite is added and coated with slurry at a low speed for a short time. This process preserves the uniform micron-sized pores within the system to the greatest extent possible. Through controllable mixing time, it is ensured that the slurry completely wets the entire surface of the ceramsite without over-mixing, which would result in an excessively thin coating layer or exposed aggregate in some areas. The continuous slurry layer provides a strong bonding transition layer between the ceramsite and the matrix, eliminating interfacial gaps. Furthermore, the aerogel nanopores and air-entraining micropores inside the slurry have been stably formed. The coating process only coats the outside of the ceramsite with slurry and does not block the original micron-sized sound-absorbing pores inside the ceramsite. All the nano-micron-millimeter three-level gradient pores are completely preserved.

[0030] S6. Molding and Curing: The mixture obtained in S5 is poured into a mold and compacted using vibration. After compaction, a plastic film is covered on the mold surface. The mixture is cured for 24 hours at a temperature of 20±2℃ and a relative humidity ≥95%, then demolded. Curing continues under the same conditions until 28 days, yielding a silica aerogel porous cement-based sound-absorbing material. The vibration frequency is 50-100Hz, the amplitude is 0.3-0.8mm, and the vibration time is 30-60s. If injected into a sound barrier mold, a sound barrier can be constructed.

[0031] Specifically, low-frequency vibration eliminates large, isolated, and ineffective air bubbles generated by stirring, improving the connectivity of pores at all levels; at the same time, it allows the coated ceramic particles to be tightly packed, forming continuous and interconnected millimeter-level low-frequency sound-absorbing channels. The vibration parameters are controllable, preventing excessive vibration from causing tiny sound-absorbing bubbles to rise and collapse; a plastic film locks in water, preventing rapid evaporation and pore collapse during the initial molding stage; and constant temperature and high humidity standard curing ensures full hydration, significantly improving the mechanical properties and long-term stability of the finished product.

[0032] Preferably, to further improve the surface sound absorption performance, mechanical drilling or spraying of other sound-absorbing materials (pore diameter 2-5mm, pore spacing 10-20mm, pore depth 1 / 3-1 / 2 of the plate thickness) or surface grooving can be performed on the material surface to increase the surface interconnected porosity.

[0033] Hole structure design principle The hole structure design of this invention follows the principle of "multi-level holes and gradient distribution": (1) Large pores (pore diameter 0.5-2mm): formed by the gaps between specially made ceramic particles; the specially made ceramic particles serve as a rigid skeleton, and the interconnected pores formed by the accumulation of particles constitute the main channel for sound waves to enter the interior of the material. At the same time, the ceramic particles themselves have a certain open porosity (12-25%), which can further increase the connectivity of the pores. The ceramic particle size is controlled at 0.5-2.0mm, which can form a suitable large pore diameter, which is beneficial to the absorption of mid- and low-frequency sound waves.

[0034] (2) Mesopores (pore size 10-500μm): formed by micro-bubbles introduced by the air-entraining agent during the stirring process, which are evenly distributed in the cement slurry, increasing the porosity of the material and refining the pore structure. The addition of the foam stabilizer ensures the stability of the bubbles in the slurry and prevents the bubbles from breaking or merging during the molding process.

[0035] (3) Nanopores (pore size 20-100nm): Introduced by the nanopores carried by the silica aerogel particles themselves. After the aerogel is uniformly dispersed in the cement paste, its nanopore structure is preserved, and a large number of nanopore spaces are constructed in the capillary space. In addition, the pozzolanic reaction products of silica fume (CSH gel) can also further refine the pore structure at the nanoscale.

[0036] By interconnecting pores of three different scales, a gradient sound absorption mechanism is formed, consisting of "large pores capturing sound waves, medium pores dissipating sound energy, and nanopores enhancing the viscous effect," thus achieving efficient absorption of wide-band sound waves.

[0037] The technical solution adopted in this invention can achieve the following beneficial effects: 1. This invention achieves broadband and efficient absorption of low, medium and high frequency sound waves through the synergistic effect of a three-level pore structure consisting of specially made ceramic particle macropores, air-entraining mesopores and silica aerogel nanopores. When the material thickness is 4cm, the noise reduction coefficient (NRC) can reach 0.68-0.78 and the average sound absorption coefficient is ≥0.65. 2. This invention uses specially made ceramsite as a rigid skeleton to bear the main load. The pozzolanic reaction of silica fume enhances the interfacial bonding strength between cement and ceramsite. Redispersible latex powder improves the toughness and adhesion of the material. It still has excellent compressive and flexural strength under high porosity, meeting the engineering mechanical requirements of walls, sound barriers and other applications. The compressive strength of the material of this invention can reach 6-12MPa, and the flexural strength is ≥2MPa, achieving a unity of high sound absorption performance and high mechanical performance. 3. This invention can control the number and size of macropores by adjusting the particle size and dosage of ceramic particles, control the mesoporosity by adjusting the dosage of air-entraining agent, and control the nanoporosity by adjusting the dosage of silica aerogel, thus achieving precise design of pore structure and adapting to different noise scenarios. 4. This invention optimizes interfacial compatibility by combining hydrophobic nano-silica aerogel with silica fume, water-reducing agent and redispersible latex powder. The aerogel does not agglomerate and the nanopores are not blocked. The internal porous structure of the material is stable for a long time after molding and will not fail due to hydration or wet-dry cycles. The aerogel is stable in dispersion and has long-lasting sound absorption. 5. This invention, by adding a water-reducing agent, produces a slurry with good fluidity, which can be poured on-site and precast into slabs. The air-entraining agent introduces microbubbles during the mixing process, and the foam stabilizer improves the stability of the bubbles in the cement slurry. Together with the interconnected macropores of the specially made ceramsite, it forms a multi-level pore structure of "macropores (ceramsite gaps) - mesopores (air-entraining bubbles) - nanopores (aerogel)," achieving efficient absorption of broadband sound waves. 6. The specially made ceramsite of this invention can utilize industrial solid waste such as fly ash as raw materials, realizing the resource utilization of solid waste and being green and environmentally friendly; the introduction of silica aerogel increases the added value of the material. 7. This invention significantly reduces the material density and building load by using specially made ceramsite and silica aerogel as dual lightweight fillers. The material of this invention can be prepared using conventional concrete molding processes, making construction simple. It is suitable for various noise control scenarios such as high-speed railway sound barriers, tunnel inner walls, building sound insulation exterior walls, urban rail transit sound-absorbing panels, and industrial plants. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0039] The terms "first," "second," "third," etc., used in the specification and claims of this application are used to distinguish similar objects and not to describe a specific order or sequence. It should be understood that such use of data can be interchanged where appropriate so that embodiments of this application can be implemented in orders other than those described herein, and the objects distinguished by "first," "second," "third," etc., are generally of the same class and the number of objects is not limited; for example, a first object can be one or more. Furthermore, in the specification and claims, "and / or" indicates at least one of the connected objects, and the character " / " generally indicates that the preceding and following objects are in an "or" relationship.

[0040] The inventive concept of this application is described here: At present, existing cement-based porous sound-absorbing materials are mainly prepared through the following methods: (1) chemical foaming method, using foaming agents such as aluminum powder and hydrogen peroxide to induce air and form pores inside the cement-based material; (2) physical foaming method, introducing air pore structure by mixing pre-made foam with cement slurry; (3) adding lightweight aggregate method, using porous aggregates such as expanded perlite and ceramsite to directly introduce pores.

[0041] However, the above method has the following technical drawbacks: First, the sound absorption bandwidth is narrow; the pore structure formed by chemical foaming and physical foaming methods is simple and the pore size distribution is concentrated, which can only have a good absorption effect on sound waves in a specific frequency band, and it is difficult to achieve effective absorption of low, medium and high frequency sound waves across the entire frequency band. Second, there is a significant contradiction between mechanical properties and sound absorption performance. Improving sound absorption requires increasing porosity, but this inevitably leads to a significant decrease in the material's compressive strength. Existing research indicates that porosity is the main factor affecting both sound absorption performance and compressive strength, and the two are often negatively correlated. Current technologies struggle to simultaneously achieve high sound absorption coefficients (NRC≥0.65) and high compressive strength (≥6 MPa). Third, the means of controlling pore structure are limited; existing technologies lack effective hierarchical control methods for the size, shape and connectivity of pores, making it difficult to construct multi-scale, multi-level pore structures that combine nanopores and micron-connected pores. Fourth, aerogels have poor compatibility with cementitious matrices. Although silica aerogels have extremely high porosity and excellent sound absorption potential, their interfacial bonding with cementitious matrices is weak. Direct incorporation will lead to a sharp decrease in material strength, limiting their application in practical engineering.

[0042] Based on this, the inventors have provided an aerogel porous cement-based sound-absorbing material and its preparation method that combines wide-band high-efficiency sound absorption, excellent mechanical properties, controllable multi-level pore structure, and good compatibility between aerogel and cement matrix. It also achieves high sound absorption coefficient and high compressive strength, and is suitable for various noise control scenarios such as high-speed railway sound barriers, tunnel inner walls, building sound insulation exterior walls, urban rail transit sound-absorbing panels, and industrial plants.

[0043] The following detailed description of the aerogel porous cement-based sound-absorbing material and its preparation method provided in this application, through specific embodiments and application scenarios, is provided in detail.

[0044] Example 1 An aerogel porous cement-based sound-absorbing material comprises, by weight, 100 parts of silicate cement (P.O42.5R), 120 parts of specially prepared ceramsite (0.5-2.0 mm particle size, gradation: 0.5-1.0 mm 30%, 1.0-1.5 mm 40%, 1.5-2.0 mm 30%), 15 parts of silica aerogel (50 nm particle size, 95% porosity), 20 parts of silica fume, 5 parts of redispersible latex powder, 2 parts of water-reducing agent, 1.2 parts of air-entraining agent, 0.25 parts of foam stabilizer, and 55 parts of water; the water-cement ratio is 0.55. A method for preparing an aerogel porous cement-based sound-absorbing material includes the following steps: S1. Pretreatment of special ceramsite: Rinse the special ceramsite with clean water to remove surface dust, soak it in water for 1.5 hours for pre-wetting treatment, take it out and drain it until it is saturated and dry, and set it aside. S2. Preparation of aerogel dispersion: 15 parts of silica aerogel powder were added to 30 parts of water, and 0.2 parts of water-reducing agent by weight of silica aerogel were added. The aerogel dispersion was prepared by a combination of high-speed shear dispersion (4000 rpm, 20 min) and ultrasonic dispersion (60 kHz, 10 min). S3. Dry material mixing: Weigh silicate cement, silica fume, and redispersible latex powder according to the mass ratio, place them in a mixer, and mix at low speed for 2 minutes to ensure that all components are fully mixed and uniform, thus obtaining a dry mixture. S4. Slurry preparation: Mix the aerogel dispersion obtained in S2 with the remaining 25 parts of water, and add the remaining 1.8 parts of water-reducing agent, air-entraining agent and foam stabilizer. After stirring evenly, slowly add it to the dry mixture obtained in S3. Stir at low speed for 1.5 min, and then stir at high speed (300 rpm) for 4 min to obtain cement cement slurry. S5, Expanded clay aggregate coating: Add the special expanded clay aggregate that has been pre-wetted in S1 to the cement slurry prepared in S4, stir for 3 minutes to make the surface of the special expanded clay aggregate uniformly coated with cement slurry to obtain the mixture. S6. Molding and Curing: The mixture prepared in S5 is poured into a 300mm×300mm×40mm mold and compacted by vibration (frequency 80Hz, time 50s). After compaction, a plastic film is covered on the surface of the mold. After curing for 24 hours at a temperature of 20±2℃ and relative humidity ≥95%, the material is demolded and cured under the same conditions until 28 days of age, thus obtaining silica aerogel porous cement-based sound-absorbing material.

[0045] Example 2 The difference between this embodiment and Embodiment 1 is that the amount of ceramsite is adjusted to 150 parts, the amount of aerogel is adjusted to 20 parts, the amount of air-entraining agent is adjusted to 1.8 parts, and the water-gel ratio is adjusted to 0.50. The remaining raw materials and preparation steps are the same as in Embodiment 1.

[0046] Example 3 The difference between this embodiment and Embodiment 1 is that the amount of ceramsite is adjusted to 90 parts, the amount of aerogel is adjusted to 10 parts, the amount of air-entraining agent is adjusted to 0.8 parts, and the water-gel ratio is adjusted to 0.45. The remaining raw materials and preparation steps are the same as in Embodiment 1.

[0047] Example 4 The difference between this embodiment and Embodiment 1 is that the aerogel content is adjusted to 20 parts, while the other raw materials and preparation steps are the same as in Embodiment 1.

[0048] Example 5 The difference between this embodiment and Embodiment 1 is that the aerogel content is adjusted to 10 parts, while the other raw materials and preparation steps are the same as in Embodiment 1.

[0049] Example 6 The difference between this embodiment and Embodiment 1 is that the amount of ceramsite is adjusted to 150 parts, while the other raw materials and preparation steps are the same as in Embodiment 1.

[0050] Comparative Example 1 The difference between this embodiment and Embodiment 1 is that silica aerogel is not added, while the other raw materials and preparation steps are the same as in Embodiment 1.

[0051] Comparative Example 2 The difference between this embodiment and Embodiment 1 is that no special ceramic particles are added; instead, an equal volume of ordinary sand is used. The remaining raw materials and preparation steps are the same as in Embodiment 1.

[0052] Comparative Example 3 The difference between this embodiment and Embodiment 1 is that the aerogel is not pre-dispersed and is directly added to the dry mixture in powder form, while the remaining proportions and preparation steps are the same as in Embodiment 1.

[0053] The compressive strength, noise reduction coefficient after 4 cm, and average sound absorption coefficient of the cement-based sound-absorbing materials of Examples 1-6 and Comparative Examples 1-3 were compared, as shown in Table 1.

[0054] Table 1: Table 1 shows that the compressive strength of Examples 1-6 of this invention is ≥7.2 MPa, meeting the requirement of ≥6 MPa, and the NRC is ≥0.69, meeting the requirement of ≥0.65. Comparative Example 1 (without aerogel) has an NRC of only 0.52 due to the lack of a nanoporous structure; Comparative Example 2 (without ceramsite skeleton) has an NRC of 0.61, but its compressive strength is only 4.5 MPa, failing to meet the mechanical performance requirements; Comparative Example 3 (aerogel not dispersed) shows a significant decrease in sound absorption performance and strength due to aerogel agglomeration. These results verify the synergistic advantages of the multi-level porous structure design of "ceramsite skeleton + aerogel nanopores + air-entraining mesopores" in this invention. Furthermore, the addition of silica aerogel gives the sound-absorbing material excellent sound absorption performance, making it suitable for various noise control scenarios such as high-speed railway sound barriers, tunnel walls, building sound insulation walls, urban rail transit sound-absorbing panels, and industrial plants.

[0055] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.

[0056] Furthermore, it should be noted that the scope of the methods and apparatus in the embodiments of this application is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. In addition, features described with reference to certain examples may be combined in other examples.

[0057] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. An aerogel porous cement-based sound-absorbing material, characterized in that, Its raw materials, by weight, include: 100 parts silicate cement, 80-150 parts special ceramsite, 5-25 parts silica aerogel, 10-30 parts silica fume, 2-8 parts redispersible latex powder, 1-3 parts water-reducing agent, 0.5-2 parts air-entraining agent, 0.1-0.5 parts foam stabilizer, and 45-65 parts water; The silica aerogel is a hydrophobic nano-silica aerogel powder with a particle size of 20-100 nm and a porosity of ≥90%.

2. The aerogel porous cement-based sound-absorbing material according to claim 1, characterized in that, The specially made ceramsite is a high-strength ceramsite that has undergone surface modification treatment. It is made from fly ash, clay or shale as raw materials, and is granulated and sintered at high temperature to produce ceramsite raw material with a particle size controlled at 0.5-2.0 mm. Then, the ceramsite raw material is soaked in an ethanol solution of silane coupling agent for 30-60 min, and then dried at 80-100℃ for 2-4 h to obtain surface-modified ceramsite.

3. The aerogel porous cement-based sound-absorbing material according to claim 1, characterized in that, The redispersible latex powder is an ethylene-vinyl acetate copolymer.

4. The aerogel porous cement-based sound-absorbing material according to claim 1, characterized in that, The water-reducing agent is a polycarboxylate water-reducing agent.

5. The aerogel porous cement-based sound-absorbing material according to claim 1, characterized in that, The air-entraining agent is rosin thermal polymer or sodium dodecyl sulfate.

6. The aerogel porous cement-based sound-absorbing material according to claim 1, characterized in that, The foam stabilizer is hydroxypropyl methylcellulose ether.

7. The method for preparing aerogel porous cement-based sound-absorbing material according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Pretreatment of special ceramsite: Rinse the special ceramsite with clean water to remove surface dust, soak it in water for 1-2 hours for pre-wetting treatment, take it out and drain it until it is saturated and dry, and set it aside. S2. Preparation of aerogel dispersion: Add silica aerogel powder to water at a mass ratio of 1:2-10, and add 0.5-2% of water-reducing agent by mass of silica aerogel. The aerogel dispersion is prepared by a combination of high-speed shear dispersion and ultrasonic dispersion. S3. Dry material mixing: Weigh silicate cement, silica fume, and redispersible latex powder according to the mass ratio, place them in a mixer, and mix at low speed for 2-3 minutes to ensure that all components are fully mixed and homogeneous, thus obtaining a dry mixture. S4. Slurry preparation: Mix the aerogel dispersion obtained in S2 with water, and add water-reducing agent, air-entraining agent and foam stabilizer. After stirring evenly, slowly add it to the dry mixture obtained in S3. Stir at low speed for 1-2 minutes, then stir at high speed for 3-5 minutes to obtain cement slurry. S5, Expanded clay aggregate coating: Add the special expanded clay aggregate that has been pre-wetted in S1 to the cement slurry prepared in S4, stir for 2-4 minutes to make the surface of the special expanded clay aggregate uniformly coated with cement slurry to obtain the mixture. S6. Molding and Curing: The mixture prepared in S5 is poured into the mold and formed by vibration compaction. After compaction, a plastic film is covered on the surface of the mold. After curing for 24 hours at a temperature of 20±2℃ and a relative humidity of ≥95%, the material is demolded and cured under the same conditions until 28 days of age, thus obtaining silica aerogel porous cement-based sound-absorbing material.

8. The method for preparing aerogel porous cement-based sound-absorbing material according to claim 7, characterized in that, In S2, the high-speed shearing speed is 3000-5000 rpm, the dispersion time is 10-30 min, the ultrasonic frequency is 40-80 kHz, and the dispersion time is 5-15 min.

9. The method for preparing aerogel porous cement-based sound-absorbing material according to claim 7, characterized in that, In S4, the low-speed stirring speed is 60-100 rpm, and the high-speed stirring speed is 200-400 rpm.

10. The method for preparing aerogel porous cement-based sound-absorbing material according to claim 7, characterized in that, In S6, the vibration frequency is 50-100Hz, the amplitude is 0.3-0.8mm, and the vibration time is 30-60s.